2020
DOI: 10.21203/rs.3.rs-126490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemical C-C Bond Cleavage of Cyclopropanes towards the Synthesis of 1,3-Difunctionalized Molecules

Abstract: Electrochemistry had a lot of inherent advantages in organic synthesis and many redox reactions have been achieved under electrochemical condition. However, the electrochemical C-C bond cleavage and functionalization reactions are less studied. Here we developed electrochemical C-C bond cleavage and 1,3-difuntionalization of arylcyclopropanes under catalyst-free and external-oxidant-free conditions. 1,3-difluorination, 1,3-oxyfluorination and 1,3-dioxygenation of arylcyclopropanes were achieved with a highly c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…S1B) and is present at all stages of the disease [15], a larger patient population may benefit from PANX1 targeted therapy. Interestingly, Pten-null cancers seem resistant to immune checkpoint inhibitory antibodies, where PTEN loss in tumor cells increases the expression of immunosuppressive cytokines inhibiting trafficking and T cell-mediated killing of tumors [57] [58]. Hence, our results point towards the direction of targeting PANX1 as a potential alternative to overcome T cell exclusion in immunosuppressive TMEs.…”
Section: Discussionmentioning
confidence: 72%
“…S1B) and is present at all stages of the disease [15], a larger patient population may benefit from PANX1 targeted therapy. Interestingly, Pten-null cancers seem resistant to immune checkpoint inhibitory antibodies, where PTEN loss in tumor cells increases the expression of immunosuppressive cytokines inhibiting trafficking and T cell-mediated killing of tumors [57] [58]. Hence, our results point towards the direction of targeting PANX1 as a potential alternative to overcome T cell exclusion in immunosuppressive TMEs.…”
Section: Discussionmentioning
confidence: 72%
“…The immunotherapy field has emphasized the targeting inhibitory receptors expressed by immune cells (58). However, recent studies suggested that the engagement of tumor-intrinsic pathways in tumor cells has been suggested as being a critical mechanism by which they restrain immunotherapydriven anti-tumor immune response (16)(17)(18)(19). It is a very important question, whether targeting tumorintrinsic pathways may be vital to extending the benefits of immunotherapy to a larger patient population, including those who thus far demonstrated immune-refractory cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that the oncogenic pathways of tumors not only promoted tumorigenesis but also interfered with the processes essential for an effective anti-tumor immunity, such as T cell trafficking to tumors and T cell-mediated killing of tumor cells (16)(17)(18)(19). For example, hyperactivation of AKT signaling by phosphatase and tensin homolog (PTEN) loss impedes the trafficking of effector T cells to tumors, reduces the sensitivity of melanoma cells to T cell-mediated killing, and is correlated with inferior outcomes of patients treated with ICB (19,20). In addition, several 4 studies have revealed that tumors commonly hijack various epigenetic mechanisms to escape immune restriction (21).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 In addition, the precise control of a minimally sufficient potential also allows better functional compatibility. 32 In particular, electrochemical methods have been demonstrated to be capable of incorporating either sulfur 33,34 or fluorine [35][36][37][38] functionalities into diverse organic frameworks. Inspired by the elegant sulfonyl fluoride (RSO2-F) synthesis via the electrochemical oxidative coupling of thiols (RSH) and potassium fluoride (KF) reported by Noël and co-workers, 39,40 we speculated that electrochemistry should be an ideal solution to simultaneously 41 introduce both fluorine and sulfur in a controllable oxidation state into alkenes.…”
Section: Scheme | Direct Incorporation Of Sulfur and Fluorine Elements Into Alkenesmentioning
confidence: 99%
“…Alkenes substituted by a naphthalene (28 and 29), alkene (30), alkyne (31), heterocycle (32)(33)(34)(35) or estrone derivative (36) also underwent the desired transformations. This protocol was also readily transferred to the preparation of the analogous chlorosulfide (37) and bromosulfide (38). Furthermore, a variety of thiophenols bearing electron-donating or electronwithdrawing groups all reacted to afford the desired fluorosulfides in moderate to good yields (39-46, 38%-87%).…”
Section: Substrate Scopementioning
confidence: 99%